Automated attenuation-based tube voltage selection for body CTA: Performance evaluation of 192-slice dual-source CT. - Winklehner, Anna; Gordic, Sonja; Lauk, Eliane; Frauenfelder, Thomas; Leschka, Sebastian; Alkadhi, Hatem; Husarik, Daniela B (European Radiology, 2015)
Objective: To assess radiation dose and image quality in body CT-angiography (CTA) with automated attenuation-based tube voltage selection (ATVS) on a 192-slice dual-source CT (DSCT).Methods: Forty patients (69.5 ± 9.6 years) who had undergone body CTA with ATVS (ref.kVp 100, ref.mAs 90) using a 2x192-slice CT in single-source mode were retrospectively included. All patients had undergone prior CTA with a 2x128-slice CT and ATVS with identical imaging and contrast media protocols, serving for comparison. Images were reconstructed with iterative reconstruction at similar strength levels. Radiation dose was determined. Image quality was assessed semi-quantitatively (1:excellent, 5:non-diagnostic), aortic attenuation, noise and CNR were determined.Results: As compared to 128-slice DSCT, 192-slice DSCT selected tube voltages were lower in 30 patients (75 %), higher in 3 (7.5 %), and similar in 7 patients (17.5 %). CTDIvol was lower with 192-slice DSCT (4.7 ± 1.9 mGy vs. 5.8 ± 2.1 mGy; p < 0.001). Subjective image quality, mean aortic attenuation (342 ± 67HU vs. 268 ± 67HU) and CNR (9.8 ± 2.5 vs. 8.2 ± 2.9) were higher with 192-slice DSCT (all p < 0.01), all datasets being diagnostic.Conclusion: Our study suggests that ATVS of 192-slice DSCT for body CTA is associated with an improved image quality and further radiation dose reduction of 19 % compared to 128-slice DSCT.Key Points: • 192-slice DSCT allows imaging from 70 kVp to 150 kVp at 10 kVp increments. • 192-slice DSCT allows for radiation-dose reduction in body-CTA with ATVS. • Subjective and objective image quality increase compared to 128-slice DSCT.